ANALISIS PENGARUH KONSENTRASI PASAR, PANGSA PASAR, DAN RASIO KEUANGAN TERHADAP KINERJA KEUANGAN BANK UMUM SWASTA NASIONAL DEVISA DI INDONESIA TAHUN 2010-2014 - Saputri, Mia Rusliyanti; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2016)
The objective of this research is to analyze the effects of firm concentration ratio (CR4), market share (MS), Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Operating Efficiency (OE) on Return on Assets (ROA) as a proxy of financial performance of Foreign Exchange Commercial Banks in Indonesia between 2010 and 2014. This research uses data obtained from the annual report and financial statement published by official website of Indonesian Stock Exchange, Financial Services Authority, and official website of each banks. The population of this research are all of Foreign Exchange Commercial Banks in Indonesia. Sampling method used with purposive sampling and consist of 20 banks with largest total loans. Data analysis method used in this research is panel data regression with Fixed Effect Method and using dummy variable. This result showed that firm concentration ratio has positive effect on ROA, operating efficiency has negative effect on ROA, while market share, CAR, NPL, and LDR are not significant in ROA with a significant level at 5%. Variables in this study can explain on ROA in the amount of 80,89% and the rest explained by factors beyond this research.